Loneliness, internalizing symptoms, and inflammatory markers in adolescent COVID‐19 survivors. - Akçay, Elif; Çöp, Esra; Dinç, Gülser Senses; Göker, Zeynep; Parlakay, Aslınur Özkaya; Demirel, Betül Damla; Mutlu, Müge; Kırmızı, Begüm (Child: Care, Health & Development, 2022)
Background: Concerns about the psychiatric sequelae after COVID‐19 infection have increased as the pandemic spreads worldwide. The increase in self‐isolation during this pandemic period has also revealed the importance of feelings of loneliness. This study aimed to examine the relationship between baseline inflammation levels, internalizing symptoms, and feelings of loneliness in adolescent COVID‐19 survivors in the long term. Methods: A total of 74 adolescents (41 girls, 55.4%, mean age 14.88) and their parents were included in the study. This cross‐sectional study assessed internalizing symptoms via Revised Children's Anxiety and Depression Scale (RCADS) and feelings of loneliness using the UCLA‐loneliness scale. Baseline inflammatory markers at COVID‐19 diagnosis were collected. Logistic regression analysis was used to determine predictors for depression in adolescents. Results: The most common disorder was Major Depressive Disorder (MDD) (25.7%), and 33.8% of the adolescents were in the clinical range in at least one internalizing domain. Baseline C‐Reactive Protein (CRP) levels correlated weakly with MDD scores. Loneliness scores correlated with all internalizing symptoms, strong association with MDD scores. Loneliness, anxiety, and parental anxiety were associated with an increased likelihood of MDD. Baseline CRP positivity did not predict MDD in adolescent COVID‐19 survivors. Conclusions: This study indicates that anxiety, loneliness, and parental anxiety play an important role in adolescents' experience of depressive symptoms after COVID‐19 infection. Thus, screening parental psychopathology and loneliness in COVID‐19 survivors seems to be preventive for adolescent mental health problems.